Analisa Dan Perancangan Sistem Perekrutan Pegawai Antar Cabang Untuk Meningkatkan Kinerja HRD Dengan Menggunakan Metode PIECES - Heryanto Lesmana Lie (Fakultas Teknologi Informasi, Universitas Atma Jaya Makassar, 2018)
Bank Mega Regional Makassar is a regional office of branches in various regions such as Sulawesi, Kalimantan, Maluku and Papua. Bank Mega Regional Makassar does not have a container that can manage data applicants, consequently the performance of new employee recruitment at Bank Mega Regional Makassar less effective, because HR managers sometimes have to interview job applicants twice, this makes the interview process repetitive and takes a long time. The PIECES method is used to identify problems occurring in the recruitment process at Bank Mega Regional Makassar. The outcome of this research is an analysis and design of a new employee recruitment system between offices and offices that can assist HR managers in managing job applicant data. Development method used in this research is spiral method. This research aims to improve the performance of HRD division at Bank Mega Regional Makassar so that the recruitment process can be faster and not repeated.